128k views
4 votes
Solve (x + 4)2 – 3(x + 4) – 3 = 0 using substitution.

u = ___

A. x
B. x + 4
C. 3(x + 4)
D. (x + 4)^2
please show a little bit of work so i know your answer isn't BS

User Panch
by
6.1k points

2 Answers

3 votes

I would say that the answer is B

User Marchello
by
6.4k points
2 votes

Answer:

Option B is correct.

u= x+4

Explanation:

Solve the equation:


(x+4)^2-3(x+4)-3 = 0

Using substitution:

Let u = x+4

then;


u^2-3u-3=0 ....[1]

For a quadratic equation
ax^2+bx+c = 0 ....[2], then the solution is given by:


x = (-b \pm √(b^2-4ac))/(2a)

On comparing equation [1] and [2] we have;

a = 1 , b = -3 and c = -3

then;


u= (-(-3) \pm √((-3)^2-4(1)(-3)))/(2(1))


u= (3 \pm √(9+12))/(2)


u= (3 \pm √(21))/(2)

Substitute u = x+4

then;


x+4= (3 \pm √(21))/(2)

Subtract 4 from both sides we have;


x= (3 \pm √(21))/(2) - 4= (3 \pm √(21)-8)/(2)


x= (3 + √(21)-8)/(2)= (-5 + √(21))/(2)

and


x= (3 - √(21)-8)/(2)


x= (-5 - √(21))/(2)

Therefore, the solution for the given equation are,


x= (-5 - √(21))/(2) ,
(-5 + √(21))/(2)

User Nihal Sangeeth
by
5.5k points